Dominant entropic binding of perfluoroalkyl substances (PFASs) to albumin protein revealed by 19F NMR. (January 2021) - Fedorenko, Michael; Alesio, Jessica; Fedorenko, Anatoliy; Slitt, Angela; Bothun, Geoffrey D.
Abstract: Mechanistic insight into protein binding by poly- and perfluoroalkyl substances (PFASs) is critical to understanding how PFASs distribute and accumulate within the body and to developing predictive models within and across classes of PFASs. Fluorine nuclear magnetic resonance spectroscopy ( 19 F NMR) has proven to be a powerful, yet underutilized tool to study PFAS binding; chemical shifts of each fluorine group reflect the local environment along the length of the PFAS molecule. Using bovine serum albumin (BSA), we report dissociation constants, K d, for four common PFASs well below reported critical micelle concentrations (CMCs) − perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorohexanesulfonic acid (PFHxS), and perfluorooctanesulfonic acid (PFOS) − as a function of temperature in phosphate buffered saline. K d values were determined based on the difluoroethyl group adjacent to the anionic headgroups and the terminal trifluoromethyl groups. Our results indicate that the hydrophobic tails exhibit greater binding affinity relative to the headgroup, and that the binding affinities are generally consistent with previous results showing that greater PFAS hydrophobicity leads to greater protein binding. However, the binding mechanism was dominated by entropic hydrophobic interactions attributed to desolvation of the PFAS tails within the hydrophobic cavities of the protein and on the surface of the protein. In addition, PFNA appears to form hemimicelles on the protein surfaces below reported CMC values. This work provides a renewed approach to utilizing 19 F NMR for PFAS-protein binding studies and a new perspective on the role of solvent entropy. Graphical abstract: Image 1 Highlights: PFAS-albumin binding measured for four common PFASs found in the U.S. population. Entropic gains through desolvation revealed by 19 F NMR proportional to PFAS volume. Association constants suggesting that PFASs may compete for fatty acid binding sites. PFAS bound per protein ranged from 12 to 14 via binding site and surface adsorption.